CULTURE, RELIGION, AND ENGLISH TEACHERS’ CONTRIBUTION IN INDONESIA - Andini Linarsih (Graduate Program of Pontianak Institute of Islamic Studies, 2013)
As culture and religion are indispensable part of the Indonesian society, understanding students’ cultural and religious background constitutes one of the important factors in the success of foreign language teaching, particularly English. Non-native English speaking teachers can improve students’ English competence because they are capable of bridging the cultural and religious differences between the source language and the target language as well as providing an easy-to-understand explanation regarding the vocabulary and grammatical aspects of the source language. In addition, they can better understand the students’ needs and design a more realistic syllabus to overcome students’ language barriers. However, the role of native English speaking teachers (NESTs) can also fill the weaknesses Non-native English speaking teachers (NNESTs) face in increasing the communicative competence. Therefore, better instruction is not merely related to the native or non native concepts. It lies on the personal qualities of the teachers to apply proper language teaching methods to boost students’ communicative skills. Keywords: Native English Speaking Teachers (NESTs), Non-Native English Speaking Teachers (NNESTs), Student, Culture, Religion.